Genotype replacement of the human parainfluenza virus type 2 in Croatia between 2011 and 2017 – the role of neutralising antibodies. Issue 11 (18th June 2018) - Šantak, M.; Lang Balija, M.; Mlinarić Galinović, G.; Ljubin Sternak, S.; Vilibić-Čavlek, T.; Tabain, I.
Abstract: Previously we reported on the HPIV2 genotype distribution in Croatia 2011–2014. Here we expand this period up to 2017 and confirm that G1a genotype has replaced G3 genotype from the period 2011–2014. Our hypothesis was that the G1a-to-G3 genotype replacement is an antibody-driven event. A cross-neutralisation with anti-HPIV2 sera specific for either G1a or G3 genotype revealed the presence of genotype-specific antigenic determinants. By the profound, in silico analyses three potential B cell epitopic regions were identified in the hemagglutinin neuraminidase (regions 314–361 and 474–490) and fusion protein (region 440–484). The region identified in the fusion protein does not show any unique site between the G1a and G3 isolates, five differentially glycosylated sites in the G1a and G3 genotype isolates were identified in epitopic regions of hemagglutinin neuraminidase. All positively selected codons were found to be located either in the region 314–316 or in the region 474–490 what indicates a strong positive selection in this region and reveals that these regions are susceptible to evolutionary pressure possibly caused by antibodies what gives a strong verification to our hypothesis that neutralising antibodies are a key determinant in the inherently complex adaptive evolution of HPIV2 in the region.